Risk Communication and Community Engagement (RCCE) in Handling Stunting: A Comparative Case Study of Indonesia and China - Fajri, Choirul; Fadillah, Dani; Farihanto, Muhammad Najih (Jurnal Ilmu Komunikasi, 2024)
Stunting is a major cause of under-five child mortality due to malnutrition. According to UNICEF, in 2022, 21.6% of children in Indonesia and over 11 million children in China were stunted, particularly in rural areas. This study aims to evaluate the effectiveness of Risk Communication and Community Engagement (RCCE) in addressing stunting in both countries. RCCE involves effectively communicating stunting risks and fostering community participation in prevention and treatment efforts. A qualitative approach was employed, focusing on interpretive analysis of field data, including observations and interview with the Ministry of Health Indonesia. The findings reveal that both the Indonesian and Chinese governments have implemented commendable RCCE programs; however, their effectiveness can be further enhanced by strengthening communication, education, community participation, and monitoring. The study concludes that RCCE has significant potential to reduce stunting rates if implemented holistically and collaboratively.